Retrospective Analysis of 447 Permanent Teeth with Injury of Attachment Apparatus - H. Hecová; V. Tzigkounakis; V. Merglová; J. Stehlíková (Czech Dental Chamber, 2008)
Injury of the attachment (suspension) apparatus belongs to frequent injuries of permanent teeth. As a result of injury, periodontal fibers are damaged to various degree as well as dental pulp, cement, alveolar bone and surrounding soft tissues. The healing of individual structures is influenced by early and correct treatment of the acute injury, degree of development of the root apex and penetrability of dentin to bacteria and their toxins. The objective of the present study was to evaluate various factors associated with the injury of the attachment apparatus in 447 permanent teeth. The analysis made it clear that age of the patients at the time of injury was 7 to 65 years and the most frequent cause of the injury to permanent teeth were various sport activities, especially bicycle riding. Necrosis of the dental pulp was the most frequent consequence in the cohort under observation. From the total number of 447 injuries it became evident in 192 teeth. In the case of lateral luxations (dislocations) it occurred significantly more often in the teeth with completed development of the root (P< 0.0001). Radiological examination demonstrated obliteration of the root canal in 49 injured teeth. External resorption of the root was detected in 96 teeth, and in 23 teeth there was a surface resorption, in 24 teeth the case was a resorption with replacement of the bone and in 49 teeth there was an inflammatory resorption. This kind of resorption was most frequently found in replanted teeth (26.53%) and teeth affected by lateral luxation (11.59%). Extensive periaplical foci were encountered most often in patients over the age of 15 years, who did to adhere to recommended post-injury control examinations.